Expectations of employers in the United States for entry-level public health job skills with a bachelor’s degree: an analysis of the positions advertised in an online job portal - Kedia, Satish K.; Entwistle, Coree; Lee, Guijin; Magaña, Laura; Burke, Emily M.; Joshi, Ashish (Frontiers in Public Health, 2023)
Objectives To analyze the current public health labor market for bachelor’s-level graduates. Methods Public health-related job postings (N = 365) from across the United States were collected from an online job portal, Indeed.com, from November 7–14, 2022. Job titles, organization type, degree requirements, work experience, job location, and preferred skills for bachelor’s-level public health positions were analyzed. Results Thirty-one job titles were identified. Approximately one-third (32.33%) of postings were from the Northeastern US; 23.56% were from the Southeastern region. Thirty-five job skill categories were identified. Most jobs (92.33%) required oral and written communication skills, and 85.21% specified educational skills for public health promotion. Cultural competency, project management, and case management abilities were also highly sought. Conclusion This study revealed the needs of the public health workforce and bolstered the case that public health degree-seekers should be equipped with a set of strategic skills applicable to a range of multisectoral and multidisciplinary public health jobs. Policy implications Given the rapid changes in the field of public health, ongoing analysis of the labor market benefits educators, employers, and policymakers alike.